Science and applications of 2.5D materials: development, opportunities and challenges - Hiroki Ago; Pablo Solís-Fernández (NPG Asia Materials)
Abstract Research on two-dimensional (2D) materials has made tremendous progress reflecting their unique properties and promising applications. In this perspective, we review the novel concept of “2.5-dimensional (2.5D) materials”, which represent new opportunities to extend the field of materials science beyond 2D materials. This concept consists of controlling van der Waals interactions and using interlayer nanospaces to synthesize new materials and explore their intriguing properties. It also includes combination with other dimensional materials, the fabrication of three-dimensional (3D) architectures of 2D materials, and practical applications in our 3D everyday life. We discuss recent research based on this concept and provide future perspectives.